Classification of Avian Pathogenic Escherichia coli (APEC) and Human Uropathogenic Escherichia coli (UPEC) in Phylogenetic Groups and Association with Pathogenicity In Vivo - Rocha, Silvio Luís da Silveira; Furian, Thales Quedi; Borges, Karen Apellanis; Rocha, Daniela Tonini da; Moraes, Hamilton Luiz de Souza; Salle, Carlos Tadeu Pippi; Nascimento, Vladimir Pinheiro do (Acta Scientiae Veterinariae, 2017)
Background: Avian pathogenic E. coli (APEC) and uropathogenic E. coli (UPEC) are responsible, respectively, for avian colibacillosis and for 80% of urinary tract infections in humans. E. coli control is difficult due to the absence of a reliable method to differentiate pathogenic and commensal strains. Genetic similarity between APEC and UPEC suggests a common ancestral origin and the capability of potentially pathogenic strains to affect human health. The classification in phylogenetic groups facilitates the identification of pathogenic strains. The objective of this work was to classify APEC and UPEC E. coli strains into phylogenetic groups and to associate it with in vivo pathogenicity. Materials, Methods & Results: 460 APEC and 450 UPEC strains, stored in BHI with glycerol at -80°C, were selected. APEC strains were isolated from cellulitis, respiratory tract and poultry litter of broiler flocks from Southern Brazil. The UPEC strains from urinary tract infection were provided by a hospital in Porto Alegre. After DNA extraction, APEC and UPEC strains were classified into four phylogenetic groups (A, B1, B2 and D) by a multiplex-PCR protocol for the detection of the chuA and yjaA genes and the TspE4.C2 DNA fragment. Phylogenetic groups were associated with pathogenicity indexes (PI), presented on a scale of 0 to 10, which were previously obtained through the inoculation of APEC strains in one-day-old chicks. Phylogenetic groups were also associated with the presence of 38 virulence-associated genes. The multiplex-PCR protocol was able to differentiate 100% of the APEC and UPEC strains in the four phylogenetic groups. The majority of APEC strains were classified into phylogenetic groups D (31.1%) and B2 (24.1%). On the other hand, the majority of UPEC strains were classified into B2 (53.6%). Among APEC strains, five genes (crl, mat, ompA, fimC and fimH) were detected in more than 80% of strains in all groups. Some genes showed a significant association with specific phylogenetic groups. Gene ireA was exclusively to group D, kpsMT II and cvaC to B2 and sat was exclusively to B1. Four genes (ireA, sfa/focCD, ibeA, tsh) were detected in more than 70% of UPEC strains in all phylogenetic groups. Gene iroN1 showed a significant association exclusively to group A, and iucD, papC and irp2 to B1 group. APEC isolated from poultry litter presented significantly lower PIs than those isolated from cellulitis and from birds with respiratory signs. The average PI from B2 group was significantly higher than that of D group. In addition, the PIs of the two groups were significantly higher than those of A and B1. Discussion: The high frequency of UPEC classified as B2 is in agreement with the literature. More virulent strains are usually classified into B2 group and some of them may be classified into D group. On the other hand, the distribution of APEC isolates in phylogenetic groups is characterized by variability and it is usually related to the origin of the isolates, as observed in the study. Since E. coli strains isolated from human and poultry face similar challenges in infection establishment of extraintestinal sites, they may share some virulence genes. In this study, most of the 38 genes presented a high frequency in both APEC and UPEC strains. As the distribution of APEC strains in phylogenetic groups showed a significant association with pathogenicity, multiplex-PCR becomes an important tool for screening the pathogenicity of strains isolated from the poultry production chain.